Academic Integrity – Plagiarism and the Impact on Students’ Work - Florina-Grațiela Șchiopu-Constantin (Journal of Educational Studies, 2021)
Nowadays, the subject of Academic Integrity is largely studied and discussed about as an issue of great interest, especially because teachers in all fields want their students to know from the beginning what is expected from them in terms of fairness when it is about completing a task the students are given and respecting the requirements of fairness. The reality is that education in this field is needed, and should be grounded on a strong background, knowing that it is much easier to take the information and use it as it belongs to you, rather than do a lot of research and get to some conclusions for which you had to work many hours, days or even months. Thus, easier, and faster needs to be replaced by harder and more serious work, which will result in personal, enriching information and results. This research has as purposes to explore the reasons for which someone would commit plagiarism, to make students aware of the consequences that such an act attracts, and to observe what can be done, to prevent it. The study will be done through Qualitative research, using a focus group discussion, 7 students in the first year of PIPP, 1 from Adventus University of Cernica, Romania. The students seemed to have enough knowledge about the problem in discussion, both the act of committing plagiarism and its consequences. Drawing the conclusions after the focus group information was gathered, there could be seen some results.